Uji Aktivitas Antibakteri Sediaan Obat Kumur Dari Enzim Bromelin Ekstrak Bonggol Nanas (Ananas comosus (L.) Merr.) TERHADAP Staphylococcus aureus - Retnaningsih, Agustina; Antika, Sindi; Widianingsih, Mastuti (Jurnal Ilmiah Wahana Pendidikan, 2026)
Dental caries is one of the most prevalent oral diseases, can be associated with infection by Staphylococcus aureus. Pineapple stem is often considered waste, actually it contains bromelain enzyme with potential antimicrobial properties. This research aimed to utilize pineapple stem as a source of bromelain for mouthwash formulation, and to evaluate its antibacterial effect against Staphylococcus aureus. Bromelain was extracted using ammonium sulfate precipitation and incorporated into mouthwash formulation at concentrations of 2%, 4%, and 6%. The formulations demonstrated acceptable physical characteristics, including pale yellow color, pineapple mint aroma, refreshing mint taste, and viscosity and pH values within standard range, indicating good physical stability. Antibacterial testing using the paper disc diffusion method showed that none of the formulations produced inhibition zones, similar to the negative control. In contrast, the positive control (Betadine mouthwash) inhibited a 2.4 mm inhibition zone. These result indicate that bromelain extract from pineapple stem did not exhibit significant antibacterial activity against Staphylococcus aureus the tested conditions.